Utilization of Sanitized Human Excreta and Wood Ash for Establishing Multipurpose Ficus Thonningii Blume in a Degraded Tantalum Technosol - D. Neina (Journal of Applied Sciences and Environmental Management)
The inclusion of native trees in mine land reclamation has been promoted over the years yet that of highvalue multipurpose species for people’s livelihoods has been overlooked. Also, studies utilizing human excreta (HE), i.e. fecal matter, (FM) and human urine fertilizer HUF), and wood ash (WA) in land reclamation are scarce. Yet, these are indispensable in areas with a limited supply of organic materials and high demand for natural resources. This study evaluated the effects of HE and WA on the growth and establishment of Ficus thonningii Blume (ficus) in a pegmatite-rich tantalum Technosol. Hardwood cuttings of ficus from homesteads in  Western Rwanda were planted in 20.4 × 19 cm diameter pots containing 5 kg forest soil (FS) and 6 kg Technosol. Five treatments including No amendment; HUF alone (100 mL/pot); HUF+WA (100 mL + 60 g/pot); FM (200 g/pot); and FM+WA (200 g + 60 g/pot) were prepared in ten replicates each. Plant height, number of leaves, shoot and root biomass were determined after five and seven months after planting. The HE and WA treatments significantly increased (P = 0.003) ficus height (FS = 39 – 42 cm and Technosol = 31 – 34 cm) after seven months. Shoot biomass weights ranged from 17 – 21 g in the FS and 10 – 16 g in the Technosol. Ficus exhibited an efficient rooting system that stabilized the loose particles of the Technosol, suggesting the potential of using ficus, HE, and WA in degraded mine soil reclamation in future research.